SAUL TABORDA: DISCUSSION ON THE CRISIS, THE BEAUTY AND THE REFORMISM (1885-1944) - Southwell, Myriam; Arata, Nicolás (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
This article is a result from a research project about “Sentimental education: school aesthetics during the 1900-1950 in Argentina” founded by Agencia Nacional para la Ciencia y la Tecnología (ANPCyT) and it was developed in three argentinian universities (Buenos Aires, La Plata and Rosario). The main purpose is to analyze pedagogical thought of Saúl Taborda, who was an active intellectual from university reformism movement -widely aknowledged in Latin America- and who developed renewal challenges in schools. Three dimensions will be crucial in order to sumarize Taborda´s ideas: a proposal about comunalism, an emancipatory point of view about young people in school organization and aesthetics as a central formative dimension.